Experimental Study on Fire Behaviour in Room following the Disposition of Openings - Fidel Meskéoulé Vondou; Claude Valery Ngayihi Abbe; Justin Tégawendé Zaida; Philippe Onguene Mvogo; Ruben Mouangue (Journal of Combustion)
Many experiments have been done by authors to study the influence of the natural ventilation through openings on fire behaviour in compartments. It has been revealed that fire will be influenced by the size of existing openings which can be an open window, an open door, or both of them. Concerning the last case, the literature does not give any information about the impact of the arrangement of these openings on the behaviour of fire. The present paper aims then to carry out a comparative study of the disposition of the window compared to the door, on the behaviour of fire in a compartment. To achieve that objective, fire experiments were conducted in a reduced scale room of ​​dimensions 1.20 m × 1.20 m × 1.02 m, which can be modulated into two configurations. The first one named “PFC configuration” is the case where the open door and the open window are in nonopposite walls. The second one named “PFO configuration” is the case where these both openings are in opposite walls. After having performed several fire tests in both configurations using the same amount of diesel fuel as fire source, results revealed that the fuel burns faster in the PFC configuration compared to that in the PFO configuration. This is due to a global mass loss rate of 2.93 × 10−4kg.s−1 against 2.62 × 10−4kg.s−1, respectively. Beyond a difference of 20°C observed on the maximal temperature of burned gases located at ceiling, results also revealed the production of ghosting flames in the PFO configuration.